Grenada : Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
The statistical data on the GDP, output and prices of major agricultural export crops, consumer price index, summary finances of the central government, central government revenue and grants, and central government social expenditures of Grenada are presented. The paper also presents data on the operations of the national insurance scheme, consolidated accounts of the banking system, eastern Caribbean central bank operations, balance-of-payments estimates, direction of trade, external trade volume, selected tourism statistics, effective exchange rate indices, and related economic indices.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet